FPGA Implementation of a CORDIC-Based Joint Angle Processor for a Climbing Robot. (15th April 2013) - Juang, Ying-Shen; Sung, Tze-Yun; Ko, Lu-Ting; Li, Ching-Iang
This paper presents a novel architecture of a joint angle processor for a robot arm. The objective of the proposed coordinate, rotation, digital computer (CORDIC)-based joint angle processor is to provide a hardware solution for computing the inverse kinematic for a robot arm control system. The complicated trigonometry operation is computed by the famous CORDIC algorithm. Simulation results show that the proposed joint angle processor achieves high precision. Moreover, an efficient pipelined architecture for very large scale integration (VLSI) and field programmable gate array (FPGA) implementation is also proposed, this architecture has the advantage of saving hardware cost and power consumption. As a result, the proposed CORDIC-based joint angle processor provides a high speed inverse kinematic computation that assists the main micro-control-unit (MCU) to operate the robot arm in real time. Therefore, the motion of the robot will be very smooth, capable of powering multiple joints at same time and provide smooth walking or climbing motions.